A power supply design - Peh, Kai Yang (Nanyang Technological University, 2022)
A regulated direct current (DC) power source was created, tested, and integrated into a circuit. With the help of a rectifier, it is possible to convert an unregulated alternate current (AC) supply to a continuous DC source. Diodes and capacitors were used to build the rectifier, which then passed the unregulated output through a regulator circuit. It is to supply a device with operational power supply constraints with a stable output (voltage or current). The regulated power supply's ultimate output will be a minimal AC signal created by the ripple voltage.